Exacerbations of chronic obstructive pulmonary disease: Time to rename - Bafadhel, M; Criner, G; Dransfield, M; Janssens, W; McDonald, V; Vogelmeier, C; Russell, R (Elsevier, 2019)
In medicine, our terminology becomes fixed, with repercussions when translated between languages, discussed among health-care professionals, and converted into lay terms for patients. For example, for chronic obstructive pulmonary disease, in using COPD as an abbreviation, the letters C, O, P, and D in some languages do not exist, whereas in lay terms, chronic obstructive pulmonary disease literally means a long-term lung problem. To overcome the non-specificity of using a catch-all term that does not characterise the unique features of an individual patients' symptoms, we now try to establish phenotypes and treatable traits of COPD. Nonetheless, the respiratory health community have neglected translating the term exacerbation, an event that substantially affects morbidity and mortality in patients with COPD. Defining the exacerbation event accurately will be a great advance; however, it is also imperative to redefine the term itself and we propose that an exacerbation of COPD should be renamed a COPD crisis.